2020
DOI: 10.1177/1096348020910214
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Contemporary Negative Political Relations on Ethnic Dining Choices

Abstract: The marketing literature has demonstrated that political animosity influences consumers’ boycott intention. However, this question has rarely been examined in the hospitality setting. Thus, by utilizing cognitive appraisal theory and value-belief-norm theory, this study proposes a model to investigate the effect of animosity on ethnic dining behavior. To this end, this study examines the effect of animosity on switching intention by examining the structural relationships among anticipated negative emotions, pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…It has been reported that motivation and knowledge of ethnic food can influence attitude and behavior positively (Seo et al, 2018). Consumer psychology researchers suggests that cultural motivation with ethnic food could help affect the both utilitarian and hedonic value (Aertsens et al, 2011; J.-H. Kim & Li, 2020). However, cultural issues may not be the major driving force for all diners visiting upscale ethnic restaurants, particularly when such consumers search for information in an unfamiliar context.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that motivation and knowledge of ethnic food can influence attitude and behavior positively (Seo et al, 2018). Consumer psychology researchers suggests that cultural motivation with ethnic food could help affect the both utilitarian and hedonic value (Aertsens et al, 2011; J.-H. Kim & Li, 2020). However, cultural issues may not be the major driving force for all diners visiting upscale ethnic restaurants, particularly when such consumers search for information in an unfamiliar context.…”
Section: Discussionmentioning
confidence: 99%
“…Animosity is conceptualized as a second-order construct composed of first-order dimensions such as economic animosity (Ang et al, 2004), war animosity (Yang et al, 2018), and PA (Campo and Alvarez, 2019; Yu et al, 2020). While the type of animosity (dimension) more likely to be salient and its effects on behavioral intentions is context-specific (Sánchez et al, 2018), past research suggests PA is not only more likely to impact behavioral intentions (Riefler and Diamantopoulos, 2007) but it is also more likely than all other types of animosity to have long-term effects on tourism behavior (Yu et al, 2020) and even impact restaurant choice (Kim, 2019; Kim and Li, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%